What Does Adolescent Substance Use Look Like During the COVID-19 Pandemic? Examining Changes in Frequency, Social Contexts, and Pandemic-Related Predictors - Dumas, Tara M.; Ellis, Wendy; Litt, Dana M. (Journal of adolescent health, 2020)
The overarching goal of this study was to provide key information on how adolescents' substance use has changed since the corona virus disease (COVID)-19 pandemic, in addition to key contexts and correlates of substance use during social distancing. Canadian adolescents (n = 1,054, Mage = 16.68, standard deviation = .78) completed an online survey, in which they reported on their frequency of alcohol use, binge drinking, cannabis use, and vaping in the 3 weeks before and directly after social distancing practices had taken effect. For most substances, the percentage of users decreased; however, the frequency of both alcohol and cannabis use increased. Although the greatest percentage of adolescents was engaging in solitary substance use (49.3%), many were still using substances with peers via technology (31.6%) and, shockingly, even face to face (23.6%). Concerns for how social distancing would affect peer reputation was a significant predictor of face-to-face substance use with friends among adolescents with low self-reported popularity, and a significant predictor of solitary substance use among average and high popularity teens. Finally, adjustment predictors, including depression and fear of the infectivity of COVID-19, predicted using solitary substance use during the pandemic. Our results provide preliminary evidence that adolescent substance use, including that which occurs face to face with peers, thereby putting adolescents at risk for contracting COVID-19, may be of particular concern during the pandemic. Further, solitary adolescent substance use during the pandemic, which is associated with poorer mental health and coping, may also be a notable concern worthy of further investigation.